2016
DOI: 10.1159/000447365
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C-Creatinine Based Glomerular Filtration Rate Equation in Obese Chronic Kidney Disease Patients: Impact of Deindexation and Gender

Abstract: Background: Cystatin C is considered an alternative to creatinine to estimate glomerular filtration rate (GFR). However, studies have reported that increased adiposity is associated with a higher level of circulating cystatin C questioning the performance of estimation of GFR using cystatin C in obese subjects. Methods: We prospectively included 166 obese stages 1-5 chronic kidney disease (CKD) patients between 2013 and 2015. GFR was measured with a reference method without (measured GFR [mGFR]) and with adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Fotheringham et al found a different relation between biases and BMI for men compared with women. Moreover, our team recently showed better accuracy for women compared with men when using creatinine and cystatine C with the deindexed CKD‐EPIcreat‐cyst formula . These results may highlight the difference in body composition between men and women for both lean and fat mass.…”
Section: Discussionmentioning
confidence: 76%
“…Fotheringham et al found a different relation between biases and BMI for men compared with women. Moreover, our team recently showed better accuracy for women compared with men when using creatinine and cystatine C with the deindexed CKD‐EPIcreat‐cyst formula . These results may highlight the difference in body composition between men and women for both lean and fat mass.…”
Section: Discussionmentioning
confidence: 76%
“…Given the inherent limitation of serum creatinine and the issues related to estimating the GFR based on serum creatinine (whether via MDRD or CKD‐EPI) , other kidney filtration markers, such as serum cystatin C, are of great interest here (Table ). Indeed, the same group of investigators recently examined 166 patients with obesity and CKD stages 1 to 5, comparing CKD‐EPI equations that use cystatin C, creatinine, or their combination, and found that using cystatin C alone or in combination with creatinine was less biased, especially when eGFR was deindexed. Therefore, it can be argued that the use of serum creatinine in any eGFR formula tends to overestimate the GFR in obesity and that serum cystatin C concentration measurement should be added as a more reliable filtration marker.…”
Section: Comparing Serum Cystatin C and Creatinine As Kidney Filtratimentioning
confidence: 99%
“…Sarcopenia in subjects with neuromuscular disease is the source of systematic overestimation of GFR by creatinine-based eGFR formulas. Studies have found differences between various eGFR formulas in obese subjects[ 119 - 122 ]. One large study concluded that cystatin-based eGFR formulas are deficient in detecting CKD stage 3 or 4 in obese subjects[ 119 ].…”
Section: Limitations Of the Formulas Computing Egfrmentioning
confidence: 99%
“…One large study concluded that cystatin-based eGFR formulas are deficient in detecting CKD stage 3 or 4 in obese subjects[ 119 ]. In contrast, two smaller studies concluded that creatinine-based equations produce higher eGFR values than cystatin-based formulas and may lead to underestimation of the presence and degree of CKD[ 120 , 122 ]. The finding that sarcopenia is highly prevalent in CKD patients leading to underestimation of the degree of obesity in this patient group[ 121 ] provides an explanation for the discrepancies between cystatin-based and creatinine-based eGFR in obese subjects with CKD.…”
Section: Limitations Of the Formulas Computing Egfrmentioning
confidence: 99%